Pengaruh Product Quality, Price Dan Promotion Terhadap Keputusan Pembelian Brand Local Ortu Seight ( Studi Kasus Mahasiswa FEB Angkatan 2019-2020 Unisma ) - Andreansyah, Onky; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In today's present day period, the world of sports has gigantic request and guarantees a modern trade opportunity for companies in Indonesia. Sutoro (2018) said that the expanding intrigued and mindfulness of working out in society is right now went with by the advancement of different sorts of businesses within the field of sports such as sports gear stores and sports field centers. the reason of this ponder was to decide the impact of item quality, cost, and advancement on acquiring choices. the test in this consider summed to 94 partisipants. The comes about of this consider show that the item quality and advancement factors have a critical positive impact, whereas the cost variable has an inconsequential positive impact  Keywords: Buying Decision, Product Quality, Price And Promotion